DYRK1B haploinsufficiency in a family with metabolic syndrome and abnormal cognition. Issue 2 (16th November 2021) - Orenstein, Naama; Gofin, Yoel; Shomron, Noam; Ruhrman‐Shahar, Noa; Magal, Nurit; Hagari, Ofir; Azulay, Noy; Bazak, Lily; Goldberg, Yael; Basel‐Salmon, Lina
Abstract : A family with DYRK1B LOF variant offering to expand the phenotype beyond the metabolic syndrome.